PENINGKATAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA SMP MELALUI PEMBELAJARAN KOOPERATIF TIPE FORMULATE-SHARE-LISTEN-CREATE (FSLC) - Reflina Reflina Reflina (State Islamic University of North Sumatra, 2017)
The research was grounded by the results of previous research which showed that students' mathematical representation ability is not as expected. One of learning strategy for enhancing mathematical representation thinking ability is formulate-share-listen-create (FSLC). This study examines the enhancement of students' mathematical representation ability through the application of FSLC learning strategy. Through a quasi experiment with non-equivalent control group design involved 41 eight-grade students from a Islamic junior high school in Way Jepara. Instrument of the study consist a set of mathematical representation ability test, and observation. Data are analyzed by using t-test. The result obtained is the enhancement of students' mathematical representation ability who were taught under FSLC learning strategy is better than those who were taught under conventional learning.